2022
DOI: 10.3390/agronomy12102328
|View full text |Cite
|
Sign up to set email alerts
|

Different Drought Tolerance Strategy of Wheat Varieties in Spike Architecture

Abstract: Spike characteristics include spike length, total spikelet number per spike, number of fertile flowers, spike density, spike fertility, grain number, thousand kernel weight, the number of spikes per square meter, harvest index and the grain yield during the flowering and ripening stage. The six winter and one facultative variety differed in earliness, derived in part from the allele of the Ppd-D1 gene and phenological observation. The two sites significantly differed in the soil moisture, which varied during c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…In our present study salinity reduced spike length number of tillers, number of spikes, number of spikelets, harvest index, seed weight and biological yield because salinity destroying the membrane mechanisms of barley ( Hordeum vulgare [ 50 ]. Similar effects are shown in rice plants ( Oryza sativa L.) growing in salty soil; a significant reduction in spike length, spike number, spikelets, and tiller number is also reported [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our present study salinity reduced spike length number of tillers, number of spikes, number of spikelets, harvest index, seed weight and biological yield because salinity destroying the membrane mechanisms of barley ( Hordeum vulgare [ 50 ]. Similar effects are shown in rice plants ( Oryza sativa L.) growing in salty soil; a significant reduction in spike length, spike number, spikelets, and tiller number is also reported [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, glume and awn detachment led to decreases in grain weight per pot of approximately 11.2 % and 25.4 %, respectively, under normal conditions. All yield components are negatively affected by drought [ 39 ]. When wheat was exposed to adverse drought stress, the grain weight per pot decreased by 16 % and 32.2 %.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that winter wheat is more sensitive to drought in the ear emergence stage (Zarei et al, 2020). Compared to the first year, the number of spikes in the later growth stage of the second year decreased, which was not conducive to the yield formation of winter wheat in the later stage (Frantova et al, 2022). According to research conducted by , a lack of moisture during the spring season can lead to a decrease in the GN of winter wheat.…”
Section: Crop Sciencementioning
confidence: 99%